Animal cruelty as an indicator of domestic violence - Muratova, A.Zh.; Smanova, A.B.; Daurembekov, E.K. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
Animal abuse is a growing public health concern and an early indicator of domestic violence; therefore, this research paper investigates its relationship with domestic abuse. This research seeks to establish and examine the connection between animal cruelty and domestic violence, especially acts perpetrated against domestic pets, and incidents of victim-driven animal husbandry when animals become the targets of aggression in a home environment. We explore psychological, sociocultural, legal and victim-driven animal husbandry aspects as well as instances when domestic animals themselves become the targets for aggression in domestic settings. Study findings reveal an unexpected connection between animal abuse and domestic violence that could help law enforcement agencies, public organizations and professionals working in social support and psychology detect cases sooner. It would also allow victims to receive immediate assistance. This research holds great relevance for law enforcement officials as well as practitioners working within these fields of social support and psychology. Law enforcement, social services and public organizations may utilize the findings from this study to enhance procedures for detecting domestic violence as well as protecting animals from abuse.